A single relapse induces worsening of disability and health-related quality of life in patients with neuromyelitis optica spectrum disorder - Berthele, Achim; Levy, Michael; Wingerchuk, Dean M.; Pittock, Sean J.; Shang, Shulian; Kielhorn, Adrian; Royston, Minying; Sabatella, Guido; Palace, Jacqueline (Frontiers in Neurology, 2023)
Background Cumulative damage from multiple relapses in neuromyelitis optica spectrum disorder (NMOSD) is associated with poor health-related quality of life (HRQoL) and long-term disability in patients positive for anti-aquaporin 4 antibodies (AQP4+). This study assessed the effect of an individual relapse on HRQoL and disability outcomes in AQP4+ NMOSD. Methods Post hoc analyses of data pooled from the PREVENT study and its open-label extension, which evaluated the efficacy and safety of eculizumab in AQP4+ NMOSD, examined the effect of a single relapse on 3 disability and 4 HRQoL outcome measures. Assuming the effect of 1 relapse extends to multiple relapses, an extrapolation was done to assess the effect of 2 relapses on these outcomes. Results In 27 patients (placebo: n = 20; eculizumab: n = 7) experiencing an independently adjudicated relapse, 1 relapse led to significantly worse disability (modified Rankin Scale and Expanded Disability Status Scale [EDSS]) and HRQoL (36-item Short-Form Health Survey mental and physical component summaries; European Quality of Life 5-Dimension questionnaire 3-Level visual analogue scale and utility index) scores. In 4 of 7 outcomes, clinically meaningful worsening was more likely for relapsing versus non-relapsing patients (n = 116). Extrapolating the effect of 2 relapses predicted that clinically meaningful worsening was more likely in 6 out of 7 outcomes, including EDSS, for patients experiencing multiple relapses versus patients experiencing no relapses. Conclusion Findings from these clinical trial data demonstrate that a single NMOSD relapse can worsen disability and HRQoL, underscoring the role of relapse prevention in improving long-term outcomes in patients with AQP4+ NMOSD.